2015
DOI: 10.1039/c4gc02184c
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly high-energy MOFs: crystal structures, thermostability, insensitivity and remarkable detonation performances

Abstract: Three environmentally friendly MOF-based HEDMs with high-nitrogen ligands present superior detonation properties, thermostability and insensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 74 publications
0
87
0
Order By: Relevance
“… Bar chart representation of previously reported T dec value of the six explosives, along with the T dec values of compounds 1 , 3 , 4 , 5 , and 6 . TZTR‐1: [Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole) 2 (H 2 O) 2 ] n ; TZTR‐2: {[Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole)] ⋅ H 2 O} n ; TZTR‐3: [Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole)] n ; PbTT: [Pb(Htztr) 2 (H 2 O)] n …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Bar chart representation of previously reported T dec value of the six explosives, along with the T dec values of compounds 1 , 3 , 4 , 5 , and 6 . TZTR‐1: [Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole) 2 (H 2 O) 2 ] n ; TZTR‐2: {[Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole)] ⋅ H 2 O} n ; TZTR‐3: [Cu(3‐(1 H ‐tetrazol‐5‐yl)‐1 H ‐triazole)] n ; PbTT: [Pb(Htztr) 2 (H 2 O)] n …”
Section: Resultsmentioning
confidence: 99%
“…Thermostability is essential for energetic materials, particularly for IHEs, because it is directly related to the thermals afety and furthera pplications.T herefore, good thermal performance (highert han the decomposition temperature of TATB, [58] 385 8C) should be an aim in the designo fn ovel IHEs. For this purpose, compounds 1-6 were studied by means of thermogravimetric and scanning calorimetry (TG-DSC) analysis.R esults show that all compounds undergo ac ontinuous dehydration process [40] relating to the removal of coordination water molecules and the sudden weight loss indicates their decomposition temperatures are 321, 294, 336, 324, 362, and 397 8C, respectively (see Table S2 in the Supporting Information), from which it can be deduced that the thermal stabilityo ft hese ECPs is significantly improved by the structural reinforcement increasing from 1D to 3D. Moreover,f rom TG-DSC resultsitc an also be confirmed that the thermals afety of these ECPs are superior comparedw ith high explosive HMX (287 8C).…”
Section: Thermal Decompositionmentioning
confidence: 97%
See 1 more Smart Citation
“…Up to now, 2‐diazo‐4,6‐dinitrophenol (DDNP) remains to be the mainly metal‐free primary explosive in applications . Recently, environmental problems force the development of new generation of green primary explosives, which not only requires good thermal stability, mechanical insensitivity and better performance, but also has an environmentally friendly synthesis and detonation process to decrease environmental pollution .…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have recently demonstrated the possibility of using nitrogen-rich MOFs as high explosives [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. MOFs consist of metal ions (Pb 2+ , Ag + , etc.…”
Section: Introductionmentioning
confidence: 99%